TINDAK BAHASA INTERPERSONAL DALAM WACANA INTERAKSI KELAS DI SMP NEGERI 2 POLONGBANGKENG UTARA; ANALISIS LINGUISTIK SISTEMIK FUNGSIONAL - Siti Sholeha; Andi Sukri Syamsuri; Syahruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study is to describe the frequency of occurrence in the relationship between categories according to the Verbal Interaction Catagory System (VICS). The suitability of verbal interactions that occur between VICS according to Flanders and pedagogical acts according to Siregar. Communication patterns in classroom interactions in the teaching and learning process of Indonesian language subjects on personal letters and official letters in class VII A of SMP Negeri 2 Polongbangkeng Utara. This study uses a qualitative descriptive method. The data sources in this study are data in the form of words, sentences and discourses contained in interpersonal speech in the classroom interaction discourse of SMP Negeri 2 Polongbangkeng Utara. The dimensional relationships that often appear are (2-7a), namely the teacher directs the learner, this can be seen during the learning process. The role of the teacher in the teaching and learning process of official letters and personal letters as a provider of direction and information can be seen from the large number of areas A that appear at 17.70% of all interactions that occur in the classroom. This proves the occurrence of active learning where students are fully involved in the teaching and learning process while the teacher is a facilitator. There is a match between the results of verbal interactions that occur between VICS according to Flanders and pedagogical actions according to Siregar. Where in VICS according to Siregar the discussion process dominates the verbal interactions that occur during the teaching and learning process with the role of the teacher as a provider of direction and information. Pedagogical actions that are often carried out by teachers during the teaching and learning process are in the form of directing motives and informing motives. In class interactions that occur in the teaching and learning process of Indonesian language subjects on official letters and personal letters, a multi-directional communication pattern or transactional communication pattern occurs. Where there is interaction between teachers and students, students and students during the teaching and learning process.